Laughing at the Devil : Seeing the World with Julian of Norwich - Hall, Amy Laura (Book collections on Project MUSE., 2018)
Laughing at the Devil is an invitation to see the world with a medieval visionary now known as Julian of Norwich, believed to be the first woman to have written a book in English. (We do not know her given name, because she became known by the name of a church that became her home.) Julian 'saw our Lord scorn [the Devil's] wickedness' and noted that 'he wants us to do the same.' In this impassioned, analytic, and irreverent book, Amy Laura Hall emphasizes Julian's call to scorn the Devil. Julian of Norwich envisioned courage during a time of fear. Laughing at the Devil describes how a courageous woman transformed a setting of dread into hope, solidarity, and resistance.